An Interactive View on the Development of Deictic Pointing in Infancy - Rohlfing, Katharina J.; Grimminger, Angela; Lüke, Carina (Frontiers in Psychology, 2017)
In this review, we will focus on the development of deictic pointing gestures. We propose that they are based on infants’ sensitivities to human motion. Since both conventionalized gestures and bodily movements can be interpreted as communicative, of special interest to us is how pointing gestures are employed within early social interactions. We push forward the idea of a conventionalization process taking place when the interaction partners guide infants’ participation toward joint goals. On their way to deploy pointing gestures and thus to successfully influence the partner for a specific purpose, infants need also to disengage from their own object perception or manipulation. In addition, infants accompany their gestures increasingly with verbal utterances—this form of communication is multimodal and offers the possibility to combine modalities for the purpose of expressing more complex utterances. The multimodal behavior will be picked up by caregivers and extended into linguistically more complex forms. Because of this emerging relationship to language and its social use, gestural behavior in early infancy is a powerful predictor for later language development.